PKA-Dependent Membrane Surface Recruitment of CI-AMPARs Is Crucial for BCP-Mediated Protection Against Post-acute Ischemic Stroke Cognitive Impairment - Chen, Sha; Wang, Yuchun; Wang, Xuhui; He, Meng; Zhang, Lu; Dong, Zhi (Frontiers in Neurology, 2020)
Post-acute ischemic stroke cognitive impairment frequently occurs and seriously affects patients daily activities. Recruitment of GluA2-containing Ca2+-impermeable AMPA receptors (CI-AMPARs) to hippocampal synaptic membrane surfaces was shown to trigger synaptic plasticity. Currently, the effect of CI-AMPAR trafficking on acute ischemic stroke remains poorly understood. β-Caryophyllene (BCP) has been shown to ameliorate cognitive impairment. However, the mechanism has not been characterized. In this study, a middle cerebral artery occlusion (MCAO) model was established to simulate the pathology of acute ischemic stroke. BCP reduced neurologic deficits, cerebral infarct volume, and pathological damage in MCAO mice and caused CI-AMPARs to translocate to synaptic membranes in the hippocampus; surface expression of CI-AMPARs was also decreased in MCAO mice. Furthermore, this study also showed that BCP treatment significantly activated the cAMP/PKA pathway, which is consistent with the synaptic membrane expression of CI-AMPARs. To better understand the underlying mechanisms, the PKA inhibitor H-89 was used to study the role of BCP in MCAO mice. Interestingly, H-89 treatment significantly disrupted the BCP-mediated facilitation of CI-AMPAR translocation to the synaptic membrane surface and substantially attenuated BCP-induced protection against acute ischemic stroke. Additionally, inhibition the cAMP/PKA pathway not only reduced BCP-induced inhibition of AMPAR-mediated excitatory postsynaptic currents in the hippocampal CA1 region but also decreased the effect of BCP-mediated protection against post-acute ischemic stroke cognitive impairment. Taken together, these data indicate that PKA-dependent synaptic membrane surface recruitment of CI-AMPARs is crucial for the neuroprotective effect of BCP against acute ischemic stroke and protection against post-acute ischemic stroke cognitive impairment.